Optimization Model of Location Routing Problem for Disaster Relief Distribution - Hamzani, Fitri Rezky; Sitorus, Syahriol; Efendi, Syahril (Sinkron : jurnal dan penelitian teknik informatika, 2022)
Disaster relief distribution is a very important component in the overall disaster response process. Consideration of limited funds, time pressure and surge of demand that come together increase to the complexity of the distribution process that must be done in a short time. Meanwhile, delays in the delivery of relief can lead to a decrease in the level of safety and welfare of disaster-affected victims. This paper proposes a location routing problem optimization model for disaster relief distribution with a multi-objective approach that minimizes waiting time and total costs. This model can help decision makers to determine the number and location of distribution centers which are opened and optimal vehicle routes.